Medication adherence and outcomes after paediatric kidney transplantation: results from a telemedicine-based, multimodal aftercare approach - Karaterzi, Sinem; Prüfe, Jenny; Wolff, Julia Katharina; Kanzelmeyer, Nele Kirsten; Ahlenstiel-Grunow, Thurid; Gertges, Raoul; Dehn-Hindenberg, Andrea; Nöhre, Mariel; De Zwaan, Martina; Tegtbur, Uwe; Schiffer, Mario; Pape, Lars (Frontiers in Nephrology, 2025)
BackgroundAdolescents and young adults demonstrate the poorest long-term graft survival post-kidney transplantation (KTx) due to a multifactorial aetiology. KTx360° is a multicentre, multimodal, telemedicine-based follow-up care model designed to improve transplant survival in adult and paediatric patients.MethodsThe paediatric component of the study was conducted at the Hannover study centres from May 2017 to October 2020 and is registered under the ISRCTN29416382 trial code. The post-transplant care model employed a structured approach, incorporating specialized case management, telemedicine support, psychological assessments and exercise assessments, with targeted interventions. The present study adopted a quasi-experimental, prospective, observational design. The primary endpoint was graft failure, defined as death or the initiation of long-term dialysis. The secondary endpoints were appointment and medication adherence, quality of life, and mental health. In the current study endpoints were analysed in a quasi-experimental, prospective, observational study: All secondary endpoints were analysed longitudinally over study duration in the intervention group using study data. Graft failure was investigated using claims data from participating statutory health insurance providers by a comparison of the eligible-to-treat group (patients transplanted after 2017 (after start of KTx360°) in study centres; ETT) to historical data in study centres (patients transplanted between 2012 and 2017 (before start of KTx360°); historical control group) and two external control groups (controls transplanted after 2017 external control group resp. between 2012–2017 in other KTx centres external historical control group). Descriptive analyses were performed reporting 95% confidence intervals.ResultsWe recruited 72 children/adolescents of whom 26 were incident (enrolled within the first year after KTx) and 46 prevalent (enrolled >1 year after KTx) participants. For all participants study data was collected on appointment and medication adherence, quality of life, and mental health. Claims data was available of 22 patients in the ETT, 17 patients in the historical control group, 71 patients in the external control group and 68 patients in the external historical control group (availability of data depends on number of participating insurance companies). In the initial years of the aftercare period, the study data revealed complete adherence behaviour among both prevalent and incident participants. However, a trend towards increasing non-adherence among prevalent participants compared to incident participants was observed. During the observation period in the first year following transplantation, no graft failure was observed in any of the study centre groups: the ETT and historical control group. Low levels of graft failure (3-6%) were observed in the external controls (external control group and external historical control group, other KTx centres). Patients were at increased risk for mental health issues with internalizing symptoms being most prevalent. Parents rated their children’s mental health worse than the patients themselves. While we saw general improvement over the course of the study, changes were not significant. Similar, quality of life was judged worse by-proxy than by patients. Development of quality of life over the course of study was heterogeneous.ConclusionThe present study observed slight trends of increasing non-adherence among prevalent participants. However, adherence levels remained consistently high across all groups. No graft failures were recorded during the observation period in the study centre Hannover before and after the implementation of KTx360°. Graft survival and adherence were significantly better in the paediatric participants than in adults. The present study suggests that adherence-enhancing and individualized therapies based on telemedicine may potentially be effective over the long term. Assessment of quality of life and mental health revealed an elevated probability of mental health concerns. Evidence from patients and proxies indicated that a combined assessment is an effective method of identifying patients at risk.